2015
DOI: 10.1111/boj.12353
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and historical determinants of population genetic structure and diversity in the Mediterranean shrubRosmarinus officinalis(Lamiaceae)

Abstract: Population genetic studies of widespread Mediterranean shrubs are scarce compared with those of trees and narrow endemics or studies from phylogeographical perspectives, despite the key role these species may play in Mediterranean ecosystems. Knowledge on the effect of ecological factors in shaping their genetic patterns is also limited. In this study we investigate genetic diversity and population structure across 18 populations of Rosmarinus officinalis, a Mediterranean shrubland plant. Populations were samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
(71 reference statements)
2
21
1
Order By: Relevance
“…All these features suggest a mixed mating in rosemary plants, with insect-mediated geitonogamy causing high rates of selffertilization but, at the same time, with a strong post-zygotic purging of inbred embryos that produce many apparently healthy but empty seeds. Consistently, a recent study on population genetics showed high levels of genetic diversity in 18 wild populations (Segarra-Moragues et al 2016), supporting the possibility that inbreeding depression acts at early stages of seed development. It can be then expected that most, if not all, the seedlings that rosemary plants produce in the field have originated from cross-pollination.…”
Section: Accepted Articlesupporting
confidence: 74%
See 1 more Smart Citation
“…All these features suggest a mixed mating in rosemary plants, with insect-mediated geitonogamy causing high rates of selffertilization but, at the same time, with a strong post-zygotic purging of inbred embryos that produce many apparently healthy but empty seeds. Consistently, a recent study on population genetics showed high levels of genetic diversity in 18 wild populations (Segarra-Moragues et al 2016), supporting the possibility that inbreeding depression acts at early stages of seed development. It can be then expected that most, if not all, the seedlings that rosemary plants produce in the field have originated from cross-pollination.…”
Section: Accepted Articlesupporting
confidence: 74%
“…Such phenotypic variability has been proposed to derive from the high phenotypic plasticity of plants and from the high genetic diversity within and among populations (Rosselló et al 2006;Morales 2010;Mateu-Andrés et al 2013). Significant levels of phenotypic plasticity have been long described in this species (Maffei et al 1993;Munné-Bosch & Alegre 2000, Alarcón et al 2006Zunzunegui et al 2011) and a recent population genetics study in 18 wild rosemary populations in eastern Spain showed high levels of genetic diversity and low genetic differentiation between populations even across the entire altitudinal distribution of the species and different soil types in a 6000 km 2 region (Segarra-Moragues et al 2016).…”
Section: Study Speciesmentioning
confidence: 99%
“…S. rosmarinus (2n = 24) has a wide natural distribution area, throughout the Mediterranean, and is cultivated all over the world mainly as food flower and ornamental. Otherwise, S. jordanii is an Iberio‐Maghrebian endemic species, while S. granatensis is an endemic species restricted to the southern part of the Iberian Peninsula (Morales, ; Segarra‐Moragues, Carrión Marco, Castellanos, Molina, & García‐Fayos, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the non-random movement of pollinators driven by preferences for plant traits, or micro-environmental factors, may produce heterogeneous patterns of gene flow12. These environmental factors could also affect seed germination and seedling establishment, contributing to directionally biased SGS35. Additionally, directional genetic flow from other populations could contribute to the observed pattern, but at the present we have no evidences for this to be considered as an important factor shaping SGS asymmetry.…”
Section: Discussionmentioning
confidence: 67%
“…Effects of soil heterogeneity on the pattern of genetic variation have been reported in several plant species. For example, Segarra-Moragues et al 35 have recently shown significant genetic differentiation between rosemary plants ( Rosmarinus officinalis ) growing in siliceous vs. calcareous soils. In our case, the observed fine-scale soil-SGS association could be caused by the differential performance (establishment, survival, growth) of some genotypes in slightly different edaphic conditions.…”
Section: Discussionmentioning
confidence: 99%